Octopamine Shifts the Behavioral Response From Indecision to Approach or Aversion in Drosophila melanogaster - Claßen, Gerbera; Scholz, Henrike (Frontiers in Behavioral Neuroscience, 2018)
Animals must make constant decisions whether to respond to external sensory stimuli or not to respond. The activation of positive and/or negative reinforcers might bias the behavioral response towards approach or aversion. Using a binary choice assay combined with optogenetic activation of neurons. we show that the activation of a set of octopaminergic/cholinergic neurons is sufficient to induce attraction to food odor. Octopamine release and no increase in levels of tyramine mediate this attraction. Activation of a subset of the first set of neurons causes aversion. This aversion is due to octopamine release and not tyramine, since in Tyramine--hydroxylase mutants (Th) lacking octopamine, the aversion is suppressed. We show that activation of the octopaminergic neurotransmitter system switches the attraction for ethanol-containing food odor to a less attractive food odor. Consistent with the requirement for octopamine in biasing the behavioral outcome, Th mutants fail to switch their attraction. The execution of attraction does not require octopamine but rather initiation of the behavior or a switch of the behavioral response. The attraction to ethanol also depends on octopamine. Pharmacological increases in octopamine signaling in Th mutants increase ethanol attraction, and blocking octopamine receptor function reduces ethanol attraction. Taken together, octopamine in the central brain orchestrates behavioral outcomes by biasing the decision of the animal towards food odors. This finding might uncover a basic principle of how octopamine gates behavioral outcomes in the brain.